Emerging AI Applications in Neonatal Surgery: A Review - Pandit, Pragati Vijaykumar; Pandit, Amruta Vijaykumar; Pagar, Prajakta Ramesh; Somvashi, Suvarna Vijaykumar; Gaikwad, Archana Sachin; Lele, Vaishali Rajeev (Journal of Neonatal Surgery, 2025)
Neonatal surgery has undergone significant advancements in recent years, with the integration of artificial intelligence (AI) and computer engineering technologies playing a pivotal role in enhancing diagnostic accuracy, surgical planning, real-time monitoring, and post-operative care. This literature review synthesizes current research on the application of AI, machine learning, computer vision, biosensors, and intelligent surgical tools in neonatal surgical interventions. The review highlights the integration of biomedical data, image analysis, and predictive modelling, illustrating how interdisciplinary innovations are driving improvements in neonatal outcomes. Additionally, ongoing challenges are discussed, and future research directions are proposed to further advance clinical practice and technology integration in neonatal surgery.